2015
DOI: 10.1007/s00330-015-3901-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of preoperative axillary ultrasonography in T1 breast tumours

Abstract: • AUS+FNA can predict axillary involvement, thus avoiding SNB. • Not all patients with axillary involvement need ALND. • Axillary tumour load determines axillary management. • AUS could classify patients according to axillary load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 52 publications
2
4
0
Order By: Relevance
“…In addition, the majority of our patients with positive needle biopsy or SLNB results had ALND; hence, the true axillary nodal status was accurately reflected. Our ultrasound sensitivity and specificity rate were also comparable with those reported in previous studies examining patients with early breast cancer [3171819].…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the majority of our patients with positive needle biopsy or SLNB results had ALND; hence, the true axillary nodal status was accurately reflected. Our ultrasound sensitivity and specificity rate were also comparable with those reported in previous studies examining patients with early breast cancer [3171819].…”
Section: Discussionsupporting
confidence: 89%
“…In additionally removed lymph nodes, metastases were found in 57.1% of the cases, while in the remaining cases, additionally removed nodes were node-negative. According to other studies in the literature, ALND followed by positive results for metastasis at SLNB showed the absence of metastasis of 38% to 67% in the remaining lymph nodes [29][30][31].…”
Section: Discussionmentioning
confidence: 59%
“…1 Although the surgical exploration of the axillary lymph nodes is required for definitive staging, axillary imaging using ultrasound and MRI has recently received renewed interest for preoperative staging in tandem with the evolving minimally invasive approaches in the investigation of the axilla. [2][3][4][5][6] Researchers have been trying to identify a subgroup of patients with breast cancer that can avoid axillary surgery in the ongoing SOUND (Sentinel Node vs Observation after Axillary Ultrasound) and INSEMA (Intergroup Sentinel Mamma) trials. [7][8][9][10] In addition, following the results of the ACOSOG (American College of Surgeons Oncology Group) Z1011 and AMAROS trials, axillary imaging is also currently expected to identify patients who can be managed appropriately with SLNB alone or ALND and with or without radiation therapy.…”
Section: Introductionmentioning
confidence: 99%